Areal artefact manufacturing using SPDT - Zhao, Junguo (Cranfield University, 2018)
With the increasing importance of the surface engineering, surface topography measuring instrument has been used in wider range of applications, which requires trustworthy calibration process to deliver traceability so that the instrument is able to give comparable and reliable measurement. The calibration standard / artefact is designed to transfer traceability easily and reliably. In current market, the feature of the artefact used for evaluation the surface topography measuring process are not sufficiently accurate. This insufficiency may be solved by using certain types of calibration standard specified in ISO standard however they are not commercially produced. In this project, one of the desired types called ‘radial sinusoidal shape’ was produce by SPDT (single point diamond turning) manufacturing method. The feature parameters of the artefact are designed to meet the instrument measurement requirement and the machining path is generated with consideration of the tooling geometry. To assess the repeatability in z direction of the turning machine, a step height experiment was designed and conducted. The measurement result indicates that the repeatability of the machine is unsatisfactory when the feed distance smaller than 100 nm. The wavelength and the amplitude of machined radial sinusoidal shape was measured by stylus profiler, followed by the measurement uncertainty analysis. The measurement result was compared with the design to evaluate quality of the manufacturing process. To estimate the systematic error of the profiler, CCI was used to measure the machined radial sinusoidal shape. The measurement result was also compared with the design.
Keywords: Surface topography measuring instrument; calibration; SPDT; measurement uncertainty; traceabililty transfer; step height